2017
DOI: 10.1039/c6ob01812b
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrative glycosylation with cyclic phosphonium anhydrides

Abstract: Cyclic phosphonium anhydrides generated from bis-phosphine oxides and trifluoromethanesulfonic anhydride are shown as general coupling reagents in a dehydrative glycosylation reaction of C1-hemiacetals. This reaction protocol is characterized by a broad substrate scope and high yields, including reactions of O-, C-, N-, and S-based nucleophiles with furanose, pyranose, and deoxysugar donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Inspired by the work of Mukaiyama and seeking to increase the viability of phosphonium salt‐assisted dehydrative glycosylation, Walczak and co‐workers investigated the efficacy of cyclic phosphonium anhydride salts as C1‐OH activators (Scheme b) . Because of their broad functional group tolerance, convenient methods of formation, and facile modulation of structural and electronic properties, this class of reagents offers advantages over other dehydrative reagents.…”
Section: Direct C1‐hydroxy Activation Using Non‐acid Electrophilic Rementioning
confidence: 98%
“…Inspired by the work of Mukaiyama and seeking to increase the viability of phosphonium salt‐assisted dehydrative glycosylation, Walczak and co‐workers investigated the efficacy of cyclic phosphonium anhydride salts as C1‐OH activators (Scheme b) . Because of their broad functional group tolerance, convenient methods of formation, and facile modulation of structural and electronic properties, this class of reagents offers advantages over other dehydrative reagents.…”
Section: Direct C1‐hydroxy Activation Using Non‐acid Electrophilic Rementioning
confidence: 98%
“…Stereoselective glycosylation that involves the possible intermediacy of a phosphonium halide intermediate was first introduced by the Mukaiyama laboratory in 2003 . Codée and co‐workers applied this strategy to rescue the poor selectivity of the glycosylation between perbenzylated glucosyl donors and primary glucosyl acceptors (Scheme ) . Here, the addition of excess triphenylphosphine oxide gives the best results in terms of stereoselectivity.…”
Section: Stereoselective Glycosylation Modulatorsmentioning
confidence: 99%
“…Together with the DMF‐modulated glycosylation with secondary acceptors, Codée's group successfully synthesized a Mycobacterium tuberculosis derived branched nonasaccharide . Very recently, a phosphonium‐modulated glycosylation was also reported by Walczak's group, which achieved high α‐selectivity with arabinose donors …”
Section: Stereoselective Glycosylation Modulatorsmentioning
confidence: 99%
“…Anomeric stannanes are also compatible with classical glycosylation conditions: we demonstrated that Schmidt‐type donors activated using TMSOTf or Pd II catalysts can reliably extend the oligosaccharide chain using anomeric nucleophiles as glycosyl acceptors. Moreover, anomeric stannanes are tolerated under dehydrative glycosylation promoted by cyclic phosphonium anhydrides and 1,2‐anhydro‐sugars can also be efficiently converted into the corresponding 2‐OH glycosides using stannanes as the glycosyl acceptors . With these conditions in hand, we were able to prepare a series of linear and branched saccharides .…”
Section: Synthesis Of Anomeric Stannanesmentioning
confidence: 99%